A Business Success Framework of Indonesian Fan-Merchandise Artists - Hanna Syaghofa; Sri Herliana (International Research Journal of Business Studies, 2025)
This study examines the entrepreneurial activities of Indonesian fan-merchandise artists and develops a business success framework. Using an abductive qualitative approach, data were collected from semi-structured interviews with 11 artists who have operated their businesses for at least 3.5 years. The findings show that business success is shaped by a combination of intrinsic and extrinsic motivation, creative management practices, personal financial resources, market engagement strategies, and community support within the meso-environment. Meanwhile, macro-environmental factors such as legal awareness and economic conditions were found to restrict rather than facilitate business success. This study proposes a modified framework consisting of Motivation, Management, Money, Market, amd Macro/Meso Environment as contextual mechanisms crucial to fan-merchandise entrepreneurship. The framework contributes to understanding passion-based micro-entrepreneurship and offers practical insights for creative industry stakeholders in Indonesia.